Experimental investigation on condensation heat transfer in a horizontal tube - Lee, Jian Yong (2017)
This project presents the internal forced convection condensation performance of different refrigerant within a condenser tube. Various condenser tube with different internal features was designed based on heat transfer principles and have been fabricated using Selective Laser Melting. The experimental data from the fabricated setup was able to match the heat transfer coefficient prediction by Shah’s Correlation accurately between 60 kg/m2·s to 140 kg/m2·s of mass flux. Experiments were conducted to investigate the heat transfer performance of bare copper condenser tube with internal diameter of 8.1mm with refrigerant R134A and R401A. Under similarly tested saturation temperature (±40oC) and vapour outlet quality (80%), the heat transfer coefficient of condenser tube for refrigerant R134A was generally higher than refrigerant R401A, with decreasing discrepancy as the tested mass flux increases. For comparison of different tested vapour outlet quality, lower tested vapour outlet quality (70%) yielded higher condensation heat transfer coefficient for both refrigerants across the tested mass flux (50 kg/m2·s - 200 kg/m2·s) compare to tested vapour outlet quality of 80%. The effect of different saturation temperature was not apparent for refrigerant R401A between saturation pressure of 1.03 MPa and 1.13 MPa, whereas the tested heat transfer coefficient for R134A is higher at lower tested saturation temperature. This could be the effect of reduced pressure is more significant than the effect of Log Mean Temperature Difference for R134A.